Макро-микроморфология нервов капсулы коленного сустава некоторых копытных - Павловский, Ю.А.; Барский, С.М. (Вестник зоологии, 1973)
It was established by means of fine anatomic preparation that the lumbo-sacral plexus nerves and sympathetic branches of truncus sympathicus, forming two zones of over¬lapping are the innervation sources of the knee joint capsule in horse, sheep and cattle. Receptor apparatuses of intraorganic nerves of joint capsule are very variable which is possibly connected with the type of support and character of locomotion in the studied animals.